Spectral derivation of the ornstein-zernike decay for four-point functions - Auil,F. (2005)
In this note we discuss the relation between the Ornstein-Zernike decay of certain four-point functions (''energy-energy correlations'') in lattice spin systems and spectral properties of the transfer matrix, related to the property of two-particle asymptotic completeness in (massive) Euclidean lattice quantum field theories.